Analysis of Thermoelastic Failure Mechanism of High-Speed Planar Friction Components. (June 2020) - Liu, Yue; Bao, Ke; Luo, Xianjie; Liu, Chunlin
Abstract: High-speed planar friction components are widely used in the compaction machinery and vehicle industries to achieve power transmission functions. During the working process, the thermoelastic coupling state of each friction pair in the high-speed planar friction component is very complicated. The finite element numerical calculation method is used to perform transient thermoelastic analysis on the friction component, and the influence of key design parameters on its thermoelastic failure is found out, which is the foundation of structure and reliability design. Taking the multi-plate clutch of the vehicle transmission system as an example, this paper analyzes the change pattern of transient thermoelastic state of each contact surface and the impact of the fixed way on the thermoelastic state during the compaction process. Research shows that the unevenness of the initial contact pressure of the friction pair increases gradually during the compaction process, and the unevenness of the first and second contact surfaces is most obvious. When the fixed steel plate is fixed only on the outside, the thermalelasticity of the contact surface is more uneven and it is prone to thermoelastic failure.